Epistemologi Hermeneutika dalam Memahami Anemia pada Ibu Hamil: Pendekatan Teoritis dan Kontekstual di Kabupaten Ciamis - Asri Aprilia Rohman; Arlin Adam (Jurnal Keperawatan Galuh, 2025)
Anemia in pregnant women is a global health concern with serious implications for both mother and fetus. According to WHO (2016), the prevalence of anemia among pregnant women in developing countries exceeds 40%, while the Indonesian Health Survey (2023) reported a prevalence of 27.7%. In Ciamis Regency, there were 3,097 reported cases (15.5%) in 2023. Conventional approaches to addressing anemia often rely on medical and universal health policy interventions, overlooking the importance of local social and cultural contexts. This study aims to develop a theory explaining the high incidence of anemia among pregnant women in Ciamis Regency using a hermeneutic approach. It explores the subjective understanding of anemia symptoms and the influence of sociocultural factors on health-related decision-making. This qualitative research employed a case study design, with in-depth interviews conducted with 30 pregnant women. Data were analyzed hermeneutically to interpret the meanings constructed by participants regarding their experiences. The findings reveal that beyond nutritional deficiencies, social and cultural factors—such as the normalization of anemia symptoms, limited access to health services, and low awareness of medical care—significantly contribute to the high prevalence of anemia. Many rural women perceive anemia as a normal condition. Conclusion: A hermeneutic approach offers deeper insights into the contextual causes of anemia. Culturally-based health education programs are essential for effective prevention.